Number of nuclei, mitotic activity and cell length in Cladophora sp. thallus treated with cadmium and chromium - Krajewska, M. (Lodz University (Poland). Dept. of Plant Cytology and Cytochemistry) (Acta Societatis Botanicorum Poloniae, 1996)
Cladophora sp., a fresh water, filamentous, multi-nucleate alga growing 16 days in the presence of cadmium and chromium at concentrations 10** (-4)-10** (-8) M was the subject of the experiment. Chromium ions reduced the number of nuclei and mitotic activity, and disturbed the correlation between cell lenght and number of nuclei, more than cadmium ions. Moreover, both tested metals caused disappearance of cells with numerous nuclei with time of the culture. Only during the first (1-4) days of culture for both metals the concentration of 10** (-4) M and especially of 10** (-8) M increased the number of nuclei, mitotic index and the lenght of cells. Apical cells were more sensitive to metals than other thallus cells